(untitled) (Jurnal Manajemen dan Investasi (MANIVESTASI), 2020)
ABSTRACT Â The problem of this research is the lack of a supervisory role that is not yet solid, and the goal is not yet achieved in the work ability to monitor and mobilize employees and the employee’s performance is not optimal. This study aims to determine "The Effect of Supervision and Work Ability on Employee Performance of the South Sumatra High Prosecutor’s Office". This research was conducted at the South Sumatra Prosecutor’s Office. With a population of 75 people with a sample of all employees who live 75 people. The data collection techniques in this study were questionnaires and documentation. Data were analyzed using normality test, multicoloniarity, and heteroscedasticity test. And using simple linear regression hypothesis testing and multiple linear regression (determination, t test and f test). Based on the data analysis, it is known that the variables of Supervision and Work Ability jointly have a significant influence on the performance of the South Sumatra High Prosecutor’s Office with a significance value of 0.000 (0.000 <0.05). Partially Work Supervision (X1) has a significant effect on performance (Y) with a significance value of 0.000 (0.000 <0.05). Work Ability (X2) has a significant effect on performance (Y) with a significant value of 0.000 (0.000 <0.05), it can be concluded that partially selection (X2) has a positive and significant effect on performance (Y). Â Keywords: Work Supervision, Work Ability, and Employee Performance Â Â ABSTRAK Â Masalah penelitian ini adalah kurangnya peranan pengawasan yang belum mantap, dan belum tercapainya tujuan dalam kemampuan kerja untuk memantau dan menggerakan pegawainya serta kinerja pegawai yang belum optimal. Penelitian ini bertujuan untuk mengetahui â€Pengaruh Pengawasan dan Kemampuan Kerja Terhadap Kinerja Pegawai Kejaksaan Tinggi Sumatera Selatanâ€. Penelitian ini dilakukan di Kejaksaan Tinggi Sumatera Selatan. Dengan populasi 75 orang dengan sampel seluruh pegawai yang berjumah 75 orang. Teknik pengumpulan data pada penelitian adalah kuesioner dan dokumentasi. Data dianalisis dengan menggunakan uji normalitas, multikoloniaritas, dan uji heteroskedasitas. SertaÂ menggunakan pengujian hipotesis regresi linier sederhana dan regresi linier berganda (determinasi, uji t dan uji f). Berdasarkan analisis data diketahui secara bersama-sama (simultan) variabel Pengawasan dan Kemampuan Kerja memiliki pengaruh signifikan terhadap Kinerja Pegawai Kejaksaan Tinggi Sumatera Selatan dengan nilai signifikasi 0,000 (0,000 < 0,05). Secara parsial Pengawasan Kerja (X1)Â mempunyai pengaruh yang signifikan terhadap Kinerja (Y) denganÂ nilai signifikasi 0,000 (0,000 < 0,05). Kemampuan Kerja (X2) mempunyai pengaruh signifikan terhadap Kinerja (Y) dengan nilai signifikan 0,000 (0,000 <0,05), maka dapat disimpulkan bahwa secara persial seleksi (X2) berpengaruh positif dan signifikan terhadap kinerja (Y). Â Kata Kunci: Pengawasan Kerja, Kemampuan Kerja, dan Kinerja Pegawai